Review on the various chemical composition of auto-catalytic nickel plating: article - Zainuddin, Nur Asykin; Hashim, Md Amin; Hanipah, Suhaiza Hanim (2017)
Autocatalytic nickel plating, also known as electroless nickel plating is a chemical technique used to deposit a layer of nickel on an object or workpiece without the use of electric current or an external electrodes to prevent corrosion. It involves the presence of a chemical reducing agent that will reduce the nickel ions, Ni²+, to nickel metal, Ni. This study is conducted to determine the various chemical composition that exist in the industries for the electroless nickel bath solution. The recorded components of a nickel plating solution are a source of nickel ions, reducing agent, complexing agent, accelerators or buffer, stabilizers or inhibitor. The other parameter of the bath such as pH and temperature are also considered. In order to achieve the objectives, this study is done by collecting data from various journals, books or any other relevant resources for example, reports, websites, patents and manufacturing companies related to autocatalytic nickel plating process. It is hope to collect a resources from year 2004 until 2016 and any relevant data about the process, the different type of reducing agent, the different type of complexing agent, accelerators used, stabilizers or inhibitors and its quantity in the bath.